The Use of Pilates Training in Back Pain and Musculoskeletal Disorders: A Literature Review - Anita Ptak; Michał Szyc (Quality in Sport)
Introduction: Pilates is a type of physical exercise invented by Joseph Pilates. They aim to have a positive effect on the body and mind. Pilates can be performed with special machines called reformers or without any additional equipment, simply on a mat. The exercises focus on strengthening the deep muscles, including the core, which can help in the treatment of patients with back pain. In addition, they have a positive effect on maintaining correct posture and fluidity of movement. Due to the above characteristics, Pilates can be one of the pillars of therapy for back pain, musculoskeletal pain, including that associated with rheumatological diseases.